International Neuroscience Initiatives through the Lens of High-Performance Computing. - Bouchard, Kristofer E.; Aimone, James B.; Chun, Miyoung; Dean, Thomas; Denker, Michael; Diesmann, Markus; Donofrio, David D.; Frank, Loren M.; Kasthuri, Narayanan; Koch, Christof; Rubel, Oliver; Simon, Horst D.; et al. (Computer (00189162), 2018)
Neuroscience initiatives aim to develop new technologies and tools to measure and manipulate neuronal circuits. To deal with the massive amounts of data generated by these tools, the authors envision the co-location of open data repositories in standardized formats together with high-performance computing hardware utilizing open source optimized analysis codes.